PROBLEMATIKA PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN ALTERNATIF PEMECAHANANNYA - Sholikhah, Octarina Hidayatus (Universitas PGRI Madiun, 2015)
In a cooperative learning model, students tasked to construct their own knowledgeunder the guidance of a teacher who acts as a facilitator and mediator. Onemodel of a cooperative learning is Group Investigation (GI). In its application,found the problem that made the implementation of classroom teaching andlearning process is less than optimal. One of the problems that occur are not theevaluation in step group. By reviewing the existing theories and facts that arerunning in the field, has found a solution to these problems, resulting inimprovements in learning steps GI.